PENGARUH PENAMBAHAN ALKANOLAMIDA TURUNAN MINYAK KELAPA SAWIT TERHADAP SIFAT-SIFAT UJI TARIK VULKANISAT KARET ALAM BERPENGISI SILIKA - Darwis Syarifuddin Hutapea; Harry Laksana Tampubolon; Indra Surya (Talenta Publisher (Universitas Sumatera Utara), 2012)
By using semi-efficient sulfur accelerated vulcanization sistem, an investigation about function of the alkanolamide as additive material on silica filled natural rubber was carried out. Alkanolamide was made by reacted between refined bleaching deodorized palm stearin with diethanolamine. Alkanolamide was added to the natural rubber compound silica filled, which is resulted vulcanizate natural rubber filled compound and occurring increasing of tensile strength, modulusand crosslinkdensity up to 5 phr. If was added more 5 phr, so reduction of the tensile strength modulus and crosslink density.